2011
DOI: 10.2174/157488611798280924
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Side Effects of Cannabidiol, a Cannabis sativa Constituent

Abstract: Cannabidiol (CBD), a major nonpsychotropic constituent of Cannabis, has multiple pharmacological actions, including anxiolytic, antipsychotic, antiemetic and anti-inflammatory properties. However, little is known about its safety and side effect profile in animals and humans. This review describes in vivo and in vitro reports of CBD administration across a wide range of concentrations, based on reports retrieved from Web of Science, Scielo and Medline. The keywords searched were "cannabinoids", "cannabidiol" a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
380
0
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(411 citation statements)
references
References 112 publications
9
380
0
22
Order By: Relevance
“…Preclinical and clinical studies show CBD possesses a wide range of therapeutic properties, including antipsychotic, analgesic, neuroprotective, anticonvulsant, antiemetic, antioxidant, anti-inflammatory, antiarthritic, and antineoplastic properties (see [11,12,[16][17][18][19] for reviews). A review of potential side effects in humans found that CBD was well tolerated across a wide dose range, up to 1500 mg/day (orally), with no reported psychomotor slowing, negative mood effects, or vital sign abnormalities noted [20].…”
Section: Cbd Pharmacology Relevant To Anxiety General Pharmacology Anmentioning
confidence: 99%
“…Preclinical and clinical studies show CBD possesses a wide range of therapeutic properties, including antipsychotic, analgesic, neuroprotective, anticonvulsant, antiemetic, antioxidant, anti-inflammatory, antiarthritic, and antineoplastic properties (see [11,12,[16][17][18][19] for reviews). A review of potential side effects in humans found that CBD was well tolerated across a wide dose range, up to 1500 mg/day (orally), with no reported psychomotor slowing, negative mood effects, or vital sign abnormalities noted [20].…”
Section: Cbd Pharmacology Relevant To Anxiety General Pharmacology Anmentioning
confidence: 99%
“…Further on, CBD seems to be well tolerated and safe in humans, even at high doses and with chronic use [22], and can easily be combined with existing treatment regimens. However, more observations and thorough investigations are needed for assessing the potential role of CBD in this deadly disease.…”
Section: Discussionmentioning
confidence: 99%
“…Enkelte av disse produktene har et høyt innhold av THC, men inneholder lite cannabidiol. Cannabidiol har interessante medisinske egenskaper og gir antagelig liten eller ingen psykomotorisk påvirkning (20,21). Mange opplever ren THC-påvirkning som ubehagelig og foretrekker medikamenter og faktisk også rusmidler som inneholder cannabidiol (22).…”
Section: Medisinsk Behandlingunclassified